Reducción de la concentración de cadmio y plomo de aguas residuales de relaves mineros mediante la utilización de filtros litológicos - Guerrero Maza, Luz Alicia; Huanga Cuenca, Lissette Dayana (Machala : Universidad Técnica de Machala, 2022)
Adsorption is one of the most efficient techniques for removing harmful heavy metals from wastewater. The objective of this research was to develop a mixed filter based on lithological material and agroindustrial waste (banana peel, orange peel, and rice husk ashes), which allows us to reduce the concentration of lead and cadmium present in water. residuals from the extraction processes of precious metals carried out by the mining activity. The sample under study (wastewater) was collected in the El Pache mining sector, Portovelo canton, El Oro province and by graphite furnace atomic absorption spectrophotometry (GFAAS) the initial and final concentrations of cadmium and lead were determined. wastewater after the filtration process, other water quality parameters were also determined, such as: pH was determined by potentiometry, total solids by thermogravimetry, ash (thermogravimetry), turbidity by turbidimetry, apparent color by colorimetry and free cyanide by titration.
La adsorción es una de las técnicas más eficientes para eliminar metales pesados nocivos de las aguas residuales. El objetivo de la presente investigación fue desarrollar un filtro mixto a base de material litológico y residuos agroindustriales (cáscara de banano, cáscara de naranja, y cenizas de cáscara de arroz), el cual nos permite reducir la concentración de cadmio y plomo presente en aguas residuales provenientes de los procesos de extracción de metales preciosos que realiza la actividad minera. La muestra objeto de estudio (agua residual) se las recolectó en el sector minero El Pache, cantón Portovelo, provincia El Oro y mediante espectrofotometría de absorción atómica con horno de grafito (GFAAS) se determinaron las concentraciones iniciales y finales de cadmio y plomo de las aguas residuales después del proceso de filtración.
Keywords: RESIDUOS AGROINDUSTRIALES; MATERIAL LITOLÓGICO; FILTRO; CADMIO